Preparation method of high-stability PtCoIn ternary alloy fuel cell cathode catalyst
By forming a Co-N-C support on the BP2000 carbon support and adsorbing Pt, Co, In, a PtCoIn ternary alloy catalyst with a Pt atomic layer structure was prepared, which solved the problem of easy sintering and poor stability of Pt-based nanocatalysts at high temperatures, and achieved high activity and long-term stability of oxygen reduction reaction performance.
Patent Information
- Application Number
- CN202510068690.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
Existing Pt-based nanocatalysts are prone to sintering at high temperatures, have limited activity and poor stability, making it difficult to provide high activity and long-term stability under harsh fuel cell conditions.
The immersion method was used to adsorb 1,10-phenanthroline-coordinated Co ions on the BP2000 carbon support, and the Co-N-C support was formed after high-temperature carbonization treatment, and then Pt salt, Co salt, and In salt were adsorbed. After high-temperature pyrolysis, acid etching and low-temperature thermal reduction, a small-sized and highly dispersed PtCoIn ternary alloy nanocatalyst with a Pt atomic layer structure on the surface was finally obtained.
The oxygen reduction reaction performance and stability of the catalyst are significantly improved, especially under high temperature and electrochemical cycle conditions, the problems of sintering and metal dissolution are avoided, and the overall stability and durability of the catalyst are improved.
Smart Images

Figure CN119890338A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a highly stable PtCoIn ternary alloy fuel cell cathode catalyst, belonging to the field of new energy nanomaterials and catalytic technology. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are highly regarded for their high energy conversion efficiency and environmental friendliness, and play a vital role in promoting sustainable global energy development. However, the cathode oxygen reduction reaction (ORR) kinetics are sluggish, and a large amount of platinum catalyst is required to ensure the power density, efficiency and practical service life of PEMFCs. The general activity, poor durability and high cost of commercial Pt / C catalysts are currently the bottleneck for the large-scale application of PEMFCs. Alloying Pt with 3d transition metals (M, such as Fe, Co and Ni) can improve ORR activity by inducing favorable ligand and strain effects while reducing the amount of Pt. However, these Pt-based alloys will suffer from severe corrosion and dealloying under the harsh conditions of PEMFC operation, resulting in a sharp attenuation of PEMFC performance. Therefore, in order to improve the practicality and sustainability of PEMFC technology, it is necessary to develop more efficient and stable catalysts that can still provide high activity and stronger stability under these harsh conditions.
[0003] Recent studies have shown that structurally ordered intermetallic compounds play a vital role in enhancing specific orientation electronic interactions and orbital coupling, thereby effectively strengthening Pt-M bonding. The enhancement of Pt-M bonding can significantly improve the resistance of Pt alloys to dissolution and dealloying, thereby improving the overall stability of the catalyst. Generally, the interatomic order of PtM intermetallic compounds is highly positively correlated with their durability. However, the transition from disordered solid solution to ordered alloy requires overcoming high thermodynamic energy barriers. Therefore, when preparing Pt-based intermetallic compounds, it is usually necessary to balance the relationship between nanoparticle size and order, resulting in a low order of PtM alloys. In addition, there are a large number of non-directional, unsaturated, delocalized valence electrons in these intermetallic compounds, which thermodynamically promote atomic migration and the dissolution of internal M atoms. Therefore, under harsh fuel cell conditions (PH <1, cathode potential: 0.6-1.5V, battery temperature: 60-80°C), most intermetallic catalysts can barely meet the durability target of the U.S. Department of Energy (DOE) for 2025 (mass activity loss less than 40%). To overcome this challenge, an effective strategy is to selectively etch the M atoms on the surface of the Pt alloy to form a core-shell structure coated with a surface Pt atomic layer. This structure is similar to the formation of a confined layer, which minimizes the dissolution of the internal metal while ensuring catalytic activity. However, this structure will still collapse under long-term electrochemical stress, exacerbating the dissolution of the surface and internal metals, posing a fundamental challenge to improving the long-term durability of Pt alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a simple and efficient technical route, which mainly solves the problems of easy sintering, limited activity and poor stability of Pt-based nanocatalysts at high temperatures, and synthesizes a small-sized, highly dispersed and highly stable PtCoIn ternary alloy fuel cell cathode catalyst with a Pt atomic layer structure on the surface.
[0005] In order to solve the above problems, the present invention adopts the following technical solutions:
[0006] The invention provides a method for preparing a highly stable PtCoIn ternary alloy fuel cell cathode catalyst. Firstly, 1,10-phenanthroline coordinated Co ions are adsorbed on a BP2000 (Cabot) carbon carrier by an impregnation method, and then a high-temperature carbonization treatment is performed to obtain a modified Co-NC carrier. Then, Pt salt, Co salt and In salt are adsorbed. Subsequently, high-temperature pyrolysis, acid etching and low-temperature thermal reduction are performed to finally obtain a small-sized and highly dispersed PtCoIn ternary alloy nanocatalyst with a Pt atomic layer structure on the surface.
[0007] In the above technical solution, the preparation method comprises the following steps:
[0008] Step 1, adding cobalt acetate tetrahydrate Co(Ac)2·4H2O and 1,10-phenanthroline to an ethanol solution, stirring and dissolving, adding a BP2000 carrier, and then ultrasonically dispersing, stirring at room temperature, fully adsorbing the metal salt complex, and obtaining a mixed solution A;
[0009] Step 2, placing the mixed solution A in an oil bath and continuing to stir, and obtaining a BP2000-Co complex after the solvent is evaporated;
[0010] Step 3, carbonizing the BP 2000-Co composite at high temperature to obtain a modified Co-NC support;
[0011] Step 4, ultrasonically dispersing the modified Co-NC carrier in a deionized water solution, adding dropwise an aqueous solution containing chloroplatinic acid H2PtCl6·6H2O, cobalt acetate tetrahydrate Co(Ac)2·4H2O and indium nitrate hydrate In(NO3)3·xH2O while stirring, and stirring at room temperature to fully adsorb metal salt ions to obtain a mixed solution B;
[0012] Step 5, placing the mixed solution B in an oil bath and continuing to stir, and after the solvent is evaporated, a Co-NC-Pt / Co / In composite is obtained;
[0013] Step 6, pyrolyzing the Co-NC-Pt / Co / In composite at high temperature;
[0014] Step 7: The carbonized sample is subjected to acid etching, washing, vacuum drying and low-temperature carbonization treatment to obtain a L10-PtCoIn@Pt catalyst.
[0015] In the above technical scheme, in step 1, the molar ratio of Co(Ac)2·4H20 to 1,10-phenanthroline is 1:3, the mass ratio of BP2000 to 1,10-phenanthroline is 5:1, and the stirring time at room temperature is 12h.
[0016] In the above technical solution, the oil bath temperature in step 2 is 60°C.
[0017] In the above technical solution, the carbonization temperature in step 3 is 700°C, the heat treatment time is 2h, and the atmosphere is Ar.
[0018] In the above technical scheme, the molar ratio of H2PtCl6·6H2O, Co(Ac)2·4H2O and In(NO3)3·xH2O in step 4 is 1:0.9:0.4, the mass ratio of H2PtCl6·6H2O to Co-NC is 1:2, and the stirring time at room temperature is 12h.
[0019] In the above technical solution, the oil bath temperature in step 5 is 60°C.
[0020] In the above technical solution, the temperature of the high temperature heat treatment in step 6 is 800°C, the heat treatment time is 2h, and the atmosphere is Ar / H2 mixed gas.
[0021] In the above technical scheme, the acid etching conditions in step 7 are 0.1MHClO4, 60℃, 12h; after pickling, centrifugation is carried out and washing is carried out with deionized water until neutral; the vacuum drying temperature is 60℃ and the drying time is 12h; the heat treatment temperature is 400℃ and the heat treatment time is 2h, and the atmosphere is Ar / H2 mixed gas.
[0022] The present invention has the following advantages:
[0023] 1) Using 1,10-phenanthroline and Co 2+ The ions are coordinated to form a complex and then composited with BP2000, and after high-temperature carbonization, a Co-NC carrier with a single Co atom site is formed. After loading the Pt alloy, the modified carrier can strengthen the metal-carrier interaction and strengthen the anchoring of the alloy nanoparticles, thereby effectively limiting the sintering of nanoparticles at high temperatures and the migration and aggregation during the electrochemical cycle.
[0024] 2) By introducing the p-block element In into the existing PtCo intermetallic compound catalyst, a PtCoIn ternary alloy catalyst (L10-PtCoIn@Pt) with the surface of the nanoparticles covered by a Pt atomic layer was successfully prepared. The Pt atomic layer structure on the catalyst surface and the formed pd orbital hybridization significantly improved the ORR performance of the catalyst, especially the stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Detailed characterization results of the L10-PtCoIn@Pt catalyst prepared in Example 1, including (a) XRD spectrum, (b) STEM image, (c) corresponding particle size statistical distribution, and (d) AC-STEM image;
[0026] Figure 2 is the EDX element mapping distribution diagram of the L10-PtCoIn@Pt catalyst prepared in Example 1;
[0027] Figure 3 Detailed characterization results of the L10-PtCo@Pt catalyst prepared in Example 2, (a) is an XRD spectrum, (b) is a STEM image, (c) is a corresponding particle size statistical distribution diagram, and (d) is an AC-STEM image;
[0028] Figure 4The performance of L10-PtCoIn@Pt, L10-PtCo@Pt and commercial Pt / C catalysts prepared in Examples 1 and 2. (a) is a polarization curve of oxygen reduction reaction, and (b) is a corresponding mass activity bar graph. In addition, the figure also shows the polarization curve of oxygen reduction reaction before and after accelerated aging test, where part (c) of the figure is for L10-PtCo@Pt catalyst and part (d) of the figure is for L10-PtCoIn@Pt catalyst;
[0029] Figure 5 The electrocatalytic performance and durability of membrane electrodes prepared based on different catalysts are demonstrated in detail;
[0030] Figure 5 (a) is a graph showing polarization curves and power density curves of membrane electrodes prepared based on L10-PtCoIn@Pt, L10-PtCo@Pt and commercial Pt / C as cathode catalysts prepared in Examples 1 and 2;
[0031] Figure 5 (b) Polarization curve and power density curve of the membrane electrode prepared based on the L10-PtCoIn@Pt catalyst prepared in Example 1 as the cathode before and after 60,000 square wave cycles. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific implementation examples.
[0033] First, 1,10-phenanthroline-coordinated Co ions were adsorbed on the BP2000 (Cabot) carbon support by an impregnation method, followed by high-temperature carbonization to obtain a modified Co-NC support. o The adsorption of In salt and In salt, followed by high-temperature pyrolysis, acid etching and low-temperature thermal reduction, finally obtained a small-sized, highly dispersed PtCoIn ternary alloy nanocatalyst (L10-PtCoIn@Pt) with a Pt atomic layer structure on the surface.
[0034] The principle is that the modified Co-NC carrier can form a strong metal-carrier interaction with metal nanoparticles, strengthen the anchoring of alloy nanoparticles, and effectively limit the sintering of nanoparticles at high temperature, ensuring high Pt atomic utilization and electrochemically active specific surface area of the catalyst; the adsorbed In salt can also alloy with Pt and Co at high temperature to form an effective pd orbital hybridization effect; in addition, further acid washing and subsequent low-temperature carbonization can etch and remove transition metal atoms on the surface of Pt nanoalloy, and promote the migration of surface Pt atoms, thereby forming a Pt atomic layer on the surface of the Pt catalyst.
[0035] The preparation process of the highly stable PtCoIn ternary alloy fuel cell cathode catalyst is as follows:
[0036] Step 1) adding cobalt acetate tetrahydrate Co(Ac)2·4H20 and 1,10-phenanthroline to an ethanol solution, stirring and dissolving, adding a BP2000 carrier, and then ultrasonically dispersing, stirring at room temperature, and fully adsorbing the metal salt complex to obtain a mixed solution A;
[0037] Step 2) placing the mixed solution A in an oil bath and continuing to stir, and after the solvent is evaporated, a BP2000-Co complex is obtained;
[0038] Step 3) carbonizing the BP2000-Co composite at high temperature to obtain a modified Co-NC support;
[0039] Step 4) ultrasonically dispersing the modified Co-NC carrier in a deionized water solution, adding dropwise an aqueous solution containing chloroplatinic acid H2PtCl6·6H2O, cobalt acetate tetrahydrate Co(Ac)2·4H2O and indium nitrate hydrate In(N03)3·xH2O while stirring, and stirring at room temperature to fully adsorb metal salt ions to obtain a mixed solution B;
[0040] Step 5) placing the mixed solution B in an oil bath and continuing to stir, and after the solvent is evaporated, a Co-NC-Pt / Co / In composite is obtained;
[0041] Step 6) pyrolyzing the Co-NC-Pt / Co / In composite at high temperature;
[0042] Step 7) The carbonized sample is subjected to acid etching, washing, vacuum drying and low-temperature carbonization treatment to obtain a L10-PtCoIn@Pt catalyst.
[0043] In the above step 1), the molar ratio of Co(Ac)2·4H2O to 1,10-phenanthroline is 1:3, the mass ratio of BP2000 to 1,10-phenanthroline is 5:1, and the stirring time at room temperature is 12 h.
[0044] In the above step 2), the oil bath temperature is 60°C.
[0045] In the above step 3), the carbonization temperature is 700° C., the heat treatment time is 2 h, and the atmosphere is Ar.
[0046] In the above step 4), the molar ratio of H2PtCl6·6H2O, Co(Ac)2·4H2O and In(NO3)3·xH2O is 1:0.9:0.4, the mass ratio of H2PtCl6·6H2O to Co-NC is 1:2, and the stirring time at room temperature is 12 h.
[0047] In the above step 5), the oil bath temperature is 60°C.
[0048] In the above step 6), the temperature of the high temperature heat treatment is 800° C., the heat treatment time is 2 h, and the atmosphere is an Ar / H2 mixed gas.
[0049] In the above step 7), the acid etching conditions are 0.1M HClO4, 60°C, 12h; after pickling, centrifugation is performed and washing is performed with deionized water until neutral; the vacuum drying temperature is 60°C and the drying time is 12h; the heat treatment temperature is 400°C and the heat treatment time is 2h, and the atmosphere is an Ar / H2 mixed gas.
[0050] Example 1
[0051] The specific preparation steps are as follows:
[0052] 1) Add 9.2 mg Co(Ac)2·4H20 and 20 mg 1,10-phenanthroline to 20 mL ethanol solution, stir to dissolve, add 100 mg BP2000 carrier, and then perform ultrasonic dispersion, stir at room temperature for 12 h to fully adsorb the metal salt complex;
[0053] 2) placing the mixed solution in a 60°C oil bath and continuing to stir, and after the solvent is evaporated, a BP2000-Co composite is obtained;
[0054] 3) The BP 2000-Co composite was carbonized at 700 °C in an Ar atmosphere for 2 h to obtain a modified Co-NC support;
[0055] 4) 40 mg of the Co-NC carrier obtained above was ultrasonically dispersed in 20 mL of deionized water solution, and 2 mL of aqueous solution containing 21.3 mg of H2PtCl6-6H2O, 9.2 mg of Co(Ac)2·4H2O and 5.0 mg of In(N03)3·xH2O was added dropwise while stirring, and stirred at room temperature for 12 h to fully adsorb metal salt ions;
[0056] 5) placing the mixed solution in a 60° C. oil bath and continuing to stir, and after the solvent is evaporated, a Co-NC-Pt / Co / In composite is obtained;
[0057] 6) Carbonizing the Co-NC-Pt / Co / In composite at 800°C in Ar / H2 atmosphere for 2 h;
[0058] 7) The carbonized sample was etched with 0.1M HClO4 at 60°C for 12h, centrifuged, washed with deionized water until neutral, and then dried at 60°C in vacuum for 12h. Finally, it was carbonized at 400°C in an Ar / H2 atmosphere for 2h to obtain the L10-PtCoIn@Pt catalyst. Figure 1The XRD spectrum, STEM image, particle size statistical distribution diagram and AC-STEM image of the L10-PtCoIn@Pt catalyst prepared in Example 1 are shown in FIG. Figure 1 The XRD spectrum of a in the figure confirms that the metal precursor forms a PtCoIn ternary intermetallic compound after high-temperature annealing. Figure 1 Figure b shows that the prepared PtCoIn nanoparticles are evenly dispersed on the carbon support without obvious sintering. Figure 1 The statistical analysis of the particle size of c shows that the average particle size of the nanoparticles is 2.6nm, indicating that the sintering problem of metal nanoparticles at high temperatures is effectively avoided. Figure 1 The AC-STEM image in (d) shows that the prepared PtCoIn nanoparticles exhibit a core-shell structure, consisting of 2-3 layers of Pt atoms on the surface and a PtCoIn core inside. Figure 2 The EDX element mapping diagram further confirms that the In element is successfully doped into PtCo. Example 2
[0059] The steps of Example 2 are similar to those of Example 1, except that the amount of Co(Ac)2·4H2O added in step 4) is adjusted from 8 mg to 13.3 mg, and 5.0 mg In(N03)3·xH2O is not added, and other conditions remain unchanged.
[0060] Figure 3 These are the XRD spectrum, STEM image, particle size statistical distribution diagram and AC-STEM image of L10-PtCo@Pt prepared in Example 2. Figure 3 The XRD spectrum of a in the figure confirms that the metal precursor forms a PtCo intermetallic compound after high-temperature annealing. Figure 3 Figure b shows that the prepared PtCo nanoparticles are evenly dispersed on the carbon support without obvious sintering. Figure 3 The statistical analysis of the particle size of c shows that the average particle size of the nanoparticles is 2.1 nm, which confirms that the sintering problem of metal nanoparticles at high temperatures is effectively avoided. Figure 3 The AC-STEM image in middle d shows that the structure of the prepared PtCo nanoparticles is similar to that of PtCoIn, and also presents a core-shell structure consisting of a Pt atomic layer on the surface and a PtCo core inside.
[0061] Figure 4 a is the polarization curve of oxygen reduction reaction of L10-PtCoIn@Pt, L10-PtCo@Pt and commercial Pt / C catalyst prepared in Examples 1 and 2. The test conditions are: 0.1M HClO4 electrolyte, scanning speed: 10mV s -1, electrode speed: 1600rpm. The test results show that: at the same Pt metal loading, L10-PtCoIn@Pt presents the highest half-wave potential: 0.938V vs.RHE, which is 15mV and 51mV higher than L10-PtCo@Pt and commercial Pt / C catalysts, respectively. In addition, by normalizing the kinetic current density at 0.9V and the Pt loading in the catalyst, the mass activity of L10-PtCoIn@Pt can be calculated to be 1.38A mg Pt -1 , which is 1.9 and 8.1 times higher than that of L10-PtCo@Pt and commercial Pt / C catalysts, respectively. Figure 4 b), further confirming that In doping significantly improves the ORR electrocatalytic activity of L10-PtCoIn@Pt. After 60,000 cycles of accelerated aging test (voltage range: 0.6-1.0 V; O2-saturated 0.1 M HClO4 electrolyte; scan rate: 100 mV s -1 ), the half-wave potential of L10-PtCo@Pt catalyst decayed by 19mV ( Figure 4 c), while the half-wave potential of the L10-PtCoIn@Pt catalyst not only did not decay but also increased by 5 mV ( Figure 4 (d) in the figure shows that the doping of In significantly improves its durability.
[0062] Figure 5 The L10-PtCoIn@Pt, L10-PtCo@Pt and commercial Pt / C catalysts prepared in Examples 1 and 2 were used as cathodes (with a loading of 0.1 mg each). Pt cm -2 ), commercial Pt / C as anode (loading 0.1 mg Pt cm -2 ) assembled into a proton exchange membrane fuel cell test results. Figure 5 Figure a shows that under the same test conditions, the peak power density of the H2-O2 fuel cell based on the L10-PtCoIn@Pt cathode reached 1.99 W cm -2 , which is significantly better than L10-PtCo@Pt (1.57W cm -2 ) and commercial Pt / C (1.17 W cm -2 ) catalyst as the cathode of the fuel cell, indicating that the L10-PtCoIn@Pt catalyst significantly improves the fuel cell performance. After 60,000 cycles of square wave accelerated aging test (0.6V holding voltage for 3s; 0.9V holding voltage for 3s), the peak power density of the H2-O2 fuel cell based on the L10-PtCoIn@Pt cathode only decayed by 0.08W Gm -2 , at 0.8A cm -2The voltage at the current density is the same as the initial state, with almost no attenuation ( Figure 5 (b) once again confirms the extremely excellent stability of the L10-PtCo@Pt catalyst.
Claims
1. A method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst, characterized in that: After adsorbing 1,10-phenanthroline-coordinated Co ions on the BP2000 carbon carrier by impregnation method, high-temperature carbonization treatment was carried out to obtain a modified Co-NC carrier, and then Pt salt, Co salt, and In salt were adsorbed. Subsequently, after high-temperature pyrolysis, acid etching and low-temperature thermal reduction, a PtColn ternary alloy nanocatalyst with a Pt atomic layer structure on the surface was finally obtained.
2. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 1, characterized in that: The steps include: Step 1, adding cobalt acetate tetrahydrate Co(Ac)2·4H2O and 1,10-phenanthroline to an ethanol solution, stirring and dissolving, adding a BP2000 carrier, and then ultrasonically dispersing, stirring at room temperature, fully adsorbing the metal salt complex, and obtaining a mixed solution A; Step 2, placing the mixed solution A in an oil bath and continuing to stir, and obtaining a BP2000-Co complex after the solvent is evaporated; Step 3, carbonizing the BP 2000-Co composite at high temperature to obtain a modified Co-NC support; Step 4, ultrasonically dispersing the modified Co-NC carrier in a deionized water solution, adding dropwise an aqueous solution containing chloroplatinic acid H2PtCl6·6H2O, cobalt acetate tetrahydrate Co(Ac)2·4H2O and indium nitrate hydrate In(NO3)3·xH2O while stirring, and stirring at room temperature to fully adsorb metal salt ions to obtain a mixed solution B; Step 5, placing the mixed solution B in an oil bath and continuing to stir, and after the solvent is evaporated, a Co-NC-Pt / Co / In composite is obtained; Step 6, pyrolyzing the Co-NC-Pt / Co / In composite at high temperature; Step 7: The carbonized sample is subjected to acid etching, washing, vacuum drying and low-temperature carbonization treatment to obtain the L10-PtColn@Pt catalyst.
3. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: In step 1, the molar ratio of Co(Ac)2·4H2O to 1,10-phenanthroline is 1:3, the mass ratio of BP2000 to 1,10-phenanthroline is 5:1, and the stirring time at room temperature is 12 h.
4. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: The oil bath temperature in step 2 was 60°C.
5. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: In step 3, the carbonization temperature is 700°C, the heat treatment time is 2h, and the atmosphere is Ar.
6. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: In step 4, the molar ratio of H2PtCl6·6H2O, Co(Ac)2·4H2O and ln(NO3)3·xH2O is 1:0.9:0.4, the mass ratio of H2PtCl6·6H2O to Co-NC is 1:2, and the stirring time at room temperature is 12 h.
7. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: The oil bath temperature in step 5 was 60°C.
8. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: In step 6, the temperature of the high temperature heat treatment is 800° C., the heat treatment time is 2 h, and the atmosphere is an Ar / H2 mixed gas.
9. The method for preparing a highly stable PtColn ternary alloy fuel cell cathode catalyst according to claim 2, characterized in that: In step 7, The acid etching conditions were 0.1 M HCIO4, 60 °C, 12 h; After acid washing, centrifuge and wash with deionized water until neutral; The vacuum drying temperature was 60°C and the drying time was 12 h; The low-temperature carbonization treatment temperature is 400°C, the heat treatment time is 2h, and the atmosphere is Ar / H2 mixed gas.
Citation Information
Cited By
High-dispersion platinum group metal-transition metal mesoporous carbon catalyst as well as preparation method and application thereof
CN121394437A